2009
DOI: 10.1016/j.scriptamat.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain boundary engineering on microstructural stability during annealing

Abstract: This is an author-produced, peer-reviewed version of this article. ABSTRACTGrain boundary engineering, which increases the special boundary fraction, may improve microstructural stability during annealing. Different processing routes are undertaken to establish the effectiveness of each and to better understand which microstructural features determine the resulting stability. We find that multiple cycles of grain boundary engineering result in a material that resists abnormal grain growth better than other pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Through grain boundary engineering, the fraction of low‐Σ boundaries, typically between 30% and 60% in conventionally processed materials, can be increased up to 80%. During the annealing processes of grain boundary engineering, low‐energy, lower‐mobility boundaries increase in length as higher‐mobility boundaries are consumed as a consequence of grain growth . For CoCrMo in non‐articulating surfaces such as the femoral neck and stem, a grain size on the coarser end of the allowable range (∼50 μm) may be ideal since these implant–tissue interfaces are subject to corrosion but not mechanical wear.…”
Section: Discussionmentioning
confidence: 99%
“…Through grain boundary engineering, the fraction of low‐Σ boundaries, typically between 30% and 60% in conventionally processed materials, can be increased up to 80%. During the annealing processes of grain boundary engineering, low‐energy, lower‐mobility boundaries increase in length as higher‐mobility boundaries are consumed as a consequence of grain growth . For CoCrMo in non‐articulating surfaces such as the femoral neck and stem, a grain size on the coarser end of the allowable range (∼50 μm) may be ideal since these implant–tissue interfaces are subject to corrosion but not mechanical wear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown GBE to be a successful method in mitigating intergranular stress corrosion cracking, 11,12 IGC, 5,13,14 hydrogen embrittlement, 15 and grain growth. 16 GBE is typically associated with the increase in specific coincidence site lattice (CSL) GBs, which have been considered special boundaries. 4 Early research within the field of GBE described some or all low Σ CSL GBs as special.…”
Section: Introductionmentioning
confidence: 99%
“…Reed showed a direct relationship between the TRD length scale and material performance [19]. Others have correlated enhancing of mechanical properties [20,21], electronic properties [22e24], and grain growth stagnation [25,26] with grain boundary engineering processing steps. Given that TRD development is a consequence of grain boundary engineering, these results likely indirectly correlate with TRD development as well.…”
Section: Introductionmentioning
confidence: 99%